2021
DOI: 10.3390/jpm11121327
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Profile and Feature Selection Comparison in Diabetic Retinopathy

Abstract: One of the main microvascular complications presented in the Mexican population is diabetic retinopathy which affects 27.50% of individuals with type 2 diabetes. Therefore, the purpose of this study is to construct a predictive model to find out the risk factors of this complication. The dataset contained a total of 298 subjects, including clinical and paraclinical features. An analysis was constructed using machine learning techniques including Boruta as a feature selection method, and random forest as classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The 24 studies enrolled 5596 DR patients and 17907 non-DR patients to explore the association between DR and abdominal obesity in patients with diabetes. Seventeen studies were conducted in Asia, four in Europe [ 15 18 ] and one each in Australia [ 19 ], North America [ 20 ] and Africa [ 21 ]. All studies were conducted in populations over 18 years.…”
Section: Resultsmentioning
confidence: 99%
“…The 24 studies enrolled 5596 DR patients and 17907 non-DR patients to explore the association between DR and abdominal obesity in patients with diabetes. Seventeen studies were conducted in Asia, four in Europe [ 15 18 ] and one each in Australia [ 19 ], North America [ 20 ] and Africa [ 21 ]. All studies were conducted in populations over 18 years.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies are summarized in Table 1. The search revealed that the articles that represented Latin America (LA) only focused on the Mexican population, from which studies were found focused on the analysis of the risk factors involved in the development of DR and clinical studies, finding a positive association with the levels of HDL, creatinine, glomerular filtration ratio, cholesterol [32], SBP, HbA1c, and albuminuria [33], proinflammatory cytokines such as TNF-a and IL-6 [34], mRNA such as TUBD1 [35], and others ruled out the association that could exist between DR and some integrin a2 polymorphisms [36]. In the studies in non-LA, the approach was differentiated between imaging trials analyzing values of venule caliber, arterial tortuosity, insulin dose, and duration of DM [37], while others associated it with clinical characteristics such as albuminuria [38,39], another focused on morphometric values such as body mass index and waist circumference [40], and another was related to conditions that may be important factors in DR such as psoriasis [41].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the Latin American analysis did not show a significant difference between DBP pressures and the presence of DR (p = 0.54) (C). Maximum Likelihood Model (MLE) [32][33][34][35][36][37][38][39]41].…”
Section: ) (A) the Exclusion Ofmentioning
confidence: 99%
“…By using Boruta wrapper feature selection algorithms with CART decision tree, [19] have improved the classification accuracy of medical datasets effectively. Moreover, Boruta has been used to identify the significant features of medical datasets [10], [22], [23], [25]. The researchers recommended Boruta to select relevant variables in high-dimensional datasets [37], [38].…”
Section: A Identifying the Important Variablesmentioning
confidence: 99%